Monitoring Uji Kualitas Udara Dan Tingkat Kebisingan Di SMAN 1 Semarapura Kabupaten Klungkung - I Made Satya Graha; Ni Luh Widyasari (Jurnal Ecocentrism, 2023)
Air pollution occurs due to the amount of pollutants that exceed the maximum limit affecting ambient air quality. Pollutant gases are produced predominantly from uncontrolled community activities, one of which is using transportation facilities. Air quality test research has been carried out at SMAN 1 Semarapura, Klungkung Regency, in the context of observing a river safety development project. Based on the analysis, the results obtained from air quality measurements for the parameter sulfur dioxide (SO2) 37.5 μg/m3; nitrogen dioxide (NO2) 6.5 μg/m3; oxidant (O3) 6.8 μg/m3; carbon monoxide (CO) 1150 μg/m3; lead (Pb) 0.002 μg/m3; total dust (TSP) 72.3 μg/m3; hydrogen sulfide (H2S) 0.017 ppm and a noise level of 43.8 dBA. These parameter values are still below the ambient air quality standards stipulated in Peraturan Gubernur Bali No. 16 Tahun 2016. Meanwhile, the ammonia (NH3) parameter is worth 9.5 mg/m3, which exceeds the ambient air quality standard. The high concentration of ammonia gas in the air can disrupt ecosystems and the health of the human body. Ammonia gas accumulating in the body can interfere with the respiratory system and irritate the respiratory tract. Therefore it is necessary to periodically monitor air quality to overcome the impact of air pollution.